Implementasi Program Indonesia Pintar (PIP) di Kota Serang - Putri, Putri Ariviani Safitri; Ralita, Ralita Ayu Pratiwi; Risma, Risma Ramahyanti; Triya, Triya Anita; Yunizar, Yunizar Fazriyanti (Universitas Merdeka Madiun, 2024)
Implementing policies entails taking action on the part of the public or private sectors to accomplish the goals outlined in earlier policy choices. One social project in the sphere of education that aims to assist impoverished people in participating in school is the Smart Indonesia Program (PIP). Using the theories of G. Shabbir Cheema and Dennis A. Rondinelli—which take organizational resources, interorganizational relationships, environmental conditions, and the traits or skills of implementing agents—this study seeks to assess the Smart Indonesia Program's implementation in Serang City. Qualitative research methodologies and literature reviews were employed in this study. In literature research, data and information are gathered from a variety of library sources, including reference books, articles, journals, memos, and prior research findings that are pertinent to the kind of study being done. To solve the issues at hand, data collecting, processing, and reasoning tasks are methodically carried out utilizing particular approaches or strategies. Qualitative research uses a variety of current techniques and is carried out in a natural environment with the goal of interpreting the phenomena that occur. The study's is findings demonstrated that, despite certain ongoing challenges, the Smart Indonesia Program's implementation in Serang City has been doing smoothly.